TECTONOTHERMAL EVOLUTION OF THE NORTHEASTERN MARGIN OF IBERIA SINCE THE BREAK-UP OF PANGEA TO PRESENT, REVEALED BY LOW-TEMPERATURE FISSION-TRACK AND (U-TH)/HE THERMOCHRONOLOGY: A CASE HISTORY OF THE CATALAN COASTAL RANGES - Juez-Larré J.; Andriessen P.A.M. (My University, 2006)
The Catalan Coastal Ranges (CCR) form part of the northeastern Iberian Mediterranean margin. This margin typifies the transition zone between the thickened crust of the Pyrenees and Ebro Basin (32 to 40 km), and the extremely thinned continental crust of the offshore Valencia Trough (8 km). Despite intensive geological research in recent decades, the issue of the unsolved thermochronological history has hardly been addressed for the Catalan Margin. This study provides for the first time a continuous low-temperature thermochronological dataset covering the period from Late Paleozoic to present-day. More than 100 analyses have been performed in an area less than 200 km long by 50 km wide. Zircon and apatite fission-track (ZFT and AFT) results of the Hercynian basement yield cooling ages between 254 ± 41-104 ± 16 Ma and 223 ± 27-16 ± 3 Ma, respectively. Apatite (U-Th)/He ages range between 58 ± 3 and 2.0 ± 0.2 Ma. These thermochronological data provide evidence for a very active geothermal past, revealing above all an important thermal period coeval with the Triassic-Early Jurassic break-up of Pangea. Hereby we discuss and suggest various mechanisms responsible for the elevated crustal temperatures detected. This new dataset also provides new constraints on the allocation of areas where exhumation/uplift occurred synchronous with some tectonic phases, the widespread presence of hydrothermal mineralizations and the present-day overmaturity state of the Mesozoic sediments, with regard to oil potential, in the CCR. Despite the local scale of the Catalan Margin, the very detailed study here presented sheds some light on the geological implications of results from other more regional thermochronological studies on the Iberian Microplate. Studies that yield similar Mesozoic thermochronological record for areas that also experienced extensional fracturing and subsidence during the break-up of Pangea. © 2006 Elsevier B.V. All rights reserved.
Keywords: CATALAN COASTAL RANGES; EXHUMATION; GROUNDWATER FLOW; IBERIAN MICROPLATE; RIFTING; THERMOCHRONOLOGY; Мезозой::Юрская; Мезозой::Триасовая; Mesozoic::Jurassic; Mesozoic::Triassic